2016
DOI: 10.1017/s0142716416000059
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic complexity in the comprehension ofwh-questions and relative clauses in typical language development and autism

Abstract: This study investigates effects of syntactic complexity operationalized in terms of movement, intervention, and noun phrase (NP) feature similarity in the development of Aʹ-dependencies in 4-, 6-, and 8-year-old typically developing (TD) French children and children with autism spectrum disorder. Children completed an offline comprehension task testing eight syntactic structures classified in four levels of complexity: Level 0: no movement; Level 1: movement without (configurational) intervention; Level 2: mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 46 publications
6
36
0
1
Order By: Relevance
“…Future work is necessary to understand if there is a relationship between syntactic dependencies such as passives and working memory in ASD, and if so, which underlying component of working memory would be involved. Finally, the development of passives did not seem to clearly improve with age in ASD as in TD, suggesting that this delay may persist into adolescence and even adulthood, as has been reported for other studies of complex syntax in ASD (Riches et al 2010;Durrleman et al 2015).…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…Future work is necessary to understand if there is a relationship between syntactic dependencies such as passives and working memory in ASD, and if so, which underlying component of working memory would be involved. Finally, the development of passives did not seem to clearly improve with age in ASD as in TD, suggesting that this delay may persist into adolescence and even adulthood, as has been reported for other studies of complex syntax in ASD (Riches et al 2010;Durrleman et al 2015).…”
Section: Resultssupporting
confidence: 49%
“…Interestingly, the error trends reported above were observed in both the ASD-LN and ASD-LI groups, with a larger number of "Theta-role reversal" and "Observer substitutes Agent" errors found for the children with language impairment. All these incorrect responses are plausibly the result of children's difficulty with locality constraints on chain formation (Borer & Wexler 1992;Hyams & Snyder 2005Snyder & Hyams 2015), part of a more general difficulty observed in children with ASD, which echoes what is found in young TD children, for the acquisition of structures involving noncanonical word orders (Riches et al 2010;Terzi et al 2012;Durrleman et al 2015;Durrleman & Delage 2016). While comprehension rates on more complex passive structures improves smoothly in relation to age in TD children, this was not the case for children with ASD, a situation already reported for other noncanonical structures in this population (Durrleman et al 2015).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…More recently, there have been investigations into the comprehension of complex syntactic structures such as wh -questions (Zebib et al, 2013), relative clauses (Riches et al, 2010; Durrleman and Zufferey, 2013; Durrleman et al, 2015), raising and passives (Perovic et al, 2007). Durrleman et al (2016) assessed the comprehension of both relative clauses and wh -questions in French and showed that children with ASD had lower performance even on simple structures as compared with their typically-developing (TD) peers who were matched on non-verbal abilities 4 . Riches et al (2010) showed that English-speaking teenagers diagnosed with autism and concomitant language deficits made significantly more errors than their age matched TD counterparts on subject and object relative clauses when tested on a sentence repetition task.…”
Section: Introductionmentioning
confidence: 99%